Negotiating Asylum The EU Acquis, Extraterritorial Protection and the Common Market of Deflection - Noll, Gregor (The Raoul Wallenberg Institute Human Rights Library, 2000)
How is access to asylum and other forms of extraterritorial protection regulated in the European Union? Is the EU acquis in these areas in conformity with international law? Which tools does international law offer to solve collisions between both? And, finally, is law capable of bridging the foundational oppositions embedded in migration and asylum issues? This work combines the potential of legal formalism with an analytical framework drawing on political theory. It analyses the argumentative strategies used by international lawyers, and developed them further, exploiting the interpretative methodology of international law as well as elaborate discrimination arguments. The author concludes that deflecting protection seekers by means of visa requirements may constitute a violation of the European Convention of Human Rights, and that the prescriptions of international law oblige Member States to apply the Dublin Convention and the Spanish Protocol in a manner emptying it of its main control functions. The author also shows that burden-sharing remains the pivotal element in the normative dynamics behind the EU acquis, and explains why the European Court of Human Rights must be regarded as the only transnational forum for the legitimate negotiation of asylum in Europe.